Innholdsmarkedsføring Konsept, forretningsmodeller, juss, etikk og praksis - Bang, Tor (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2016)
This book describes the concept of content marketing in a Norwegian context. Its subtitle, meaning "concept, business models, legal aspects, ethics and practice", is comprised of key words for each chapter. The concept chapter includes trends and historical roots, as well as a discussion of the definition of 'content marketing'. The book is concerned about the practice of content marketing in a context where media are digitalized, and how digitalization is linked to changes in business models for the media. However, content marketing practices are challenging the legal framework as well as ethical restrictions in several ways. One example is freedom of expression concerning commercial content. Another is the debate on content marketing as native advertisements in editorial products, and the risk of mixing such commercial content with journalism. This book is the first to be published on this topic in the Norwegian language based on scientific research and including many examples from Norwegian practices.